1977
DOI: 10.1136/bmj.1.6064.817
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis, cutaneous capillaritis, and IgM-associated membranous glomerulonephritis.

Abstract: BRITISH MEDICAL JOURNAL 26 MARCH 1977 817 been a total of 19 cases in seven families reported, our patients bringing the total to 21 cases in eight families. The familial incidence of hypernephromas may be fortuitous, but if a genetic factor is present the question of screening other members of the family arises. Brinton2 and Steinberg et al3 reported hypernephroma in two generations and it would therefore seem reasonable to carry out regular five-year investigations in the other siblings and the children of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…This disorder is rarely associated with the development of nephrotic syndrome, particularly of membranous nephropathy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In this case report, we have shown that the CsA monotherapy effectively alleviated the nephrotic range proteinuria as well as liver dysfunction in a patient with PBC and membranous nephropathy.…”
Section: Discussionmentioning
confidence: 76%
“…This disorder is rarely associated with the development of nephrotic syndrome, particularly of membranous nephropathy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In this case report, we have shown that the CsA monotherapy effectively alleviated the nephrotic range proteinuria as well as liver dysfunction in a patient with PBC and membranous nephropathy.…”
Section: Discussionmentioning
confidence: 76%
“…Large complexes may fix compiement (leading to a reduced CHw) and couid be responsibie for tissue damage. A spiilovcr of CIC into the systetiiic circulation could be incidental to the pathogenetic process but may explain the association of PBC with extrahepatic conditions such as vasculitis [21], and especially between CIC and joint disease [8J. The role of CIC in the pathogenesis of PBC remains controversial [22].…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone In the patient described herein, sodium iodide I 125 therapy had been administered during the most recent admission, but had not been given at the time of initial presentation of pyoderma gangrenosum. In the setting of (1) negative bacterial cultures of lesion and blood, (2) lack of response to antibiotics, (3) pathergy, (4) iodine exacerba¬ tion, (5) evolving clinical picture, (6) history of similar lesions with residual scarring, (7) biopsy findings, (8) rapid response to prednisone, (9) and a residual cribriform scar after healing, the diagnosis of pyoderma gangrenosum was firmly established in this patient.…”
mentioning
confidence: 91%